The relationship between prevalence and duration of weight loss strategies and weight loss among overweight managed care organization members enrolled in a weight loss trial - Jeffery Robert W; Erickson Darin J; Linde Jennifer A; Pronk Nicolaas P; Boyle Raymond G (BMC, 2006)
Abstract Background Many adults in the United States report engaging in weight loss behaviors. The current study examined weight loss strategies among managed care organization members, to determine the prevalence and impact of weight loss behaviors in this population. We hypothesized that greater engagement in weight loss strategies would be associated with greater weight loss success. Methods Data were taken from Weigh-to-Be (WTB), a two-year weight loss trial (N = 1801, 72% female, mean age = 50.7 years, mean weight = 95.9 kg, mean BMI = 34.2 kg/m2). Every six months, participants completed a questionnaire assessing frequency and duration of weight loss strategies (calorie reduction, fat reduction, increased fruit/vegetable intake, increased exercise, elimination of sweets, consumption of less food). General linear models and structural equation methods were used to examine associations between weight loss strategy use and weight change over time. Results Weight loss strategy prevalence rates ranged from 68% to 76% over two years. For all dietary strategies, any use of the strategy between baseline and 24 months was associated with weight loss at 24 months; those who did not engage in the strategy showed weight gains during that period. Results of general linear models and structural equation models indicated that increased use of weight loss strategies was significantly associated with greater 24-month weight loss. Conclusion The prevalence of weight loss strategies in this obese adult managed care population was quite high, and use of these strategies was associated in dose-response fashion with better weight loss. Future interventions may benefit from emphasis on persistence of similar strategies to achieve more successful outcomes.